Pathological findings associated with stillborn babies - C, Sofiya; B., Pushpa; S., Selvi; Hemavathi, Hemavathi (International Journal of Medical Research and Review, 2016)
Introduction: Fetal death rate and Perinatal Mortality rate are important indicators of a country’s Health care system. Stillbirth forms a prime contributing factor in deciding these rates. But the causes of Stillbirth and autopsy findings associated with Stillbirth remains a gray zone. The aim of this study is to analyse the pathological autopsy findings associated with spontaneously expelled stillbirth babies and placenta. Materials and Methods: This is a retrospective study conducted in Department of Pathology, Govt. Kilpauk Medical College, Chennai for a period of 1 and half years. 29 Stillborn cases were received in our department during this period. Fetal autopsy was done in these cases by using a standard protocol. The external, internal examination findings and histopathological findings of both fetus and Placenta were analysed and compared with the Antenatal clinical findings. Results: Stillbirth is more common in the third trimester constituting 72.4% cases and peaks at 27-30 weeks of gestation. Placental pathology is more frequently associated with stillbirth with 44.8% followed by Fetal causes with 34.5% and maternal causes identified in 6.9% cases. In the second trimester stillbirths fetal causes are common and in third trimester placental pathologies were common. Among the fetal causes, congenital anamolies are seen in all cases with CNS and Kidney anamolies being the commonest. Among the Placental causes, placental infarct is seen in most of the cases. In 13.8% cases, no pathology identified even after complete autopsy. Conclusion: A Complete schematic autopsy of fetus and placenta along with a good knowledge and correlation of pathological and clinical findings help in arriving at a diagnosis of cause of fetal demise. A correct diagnosis of the cause of stillbirth can alleviate parents worries and helps the clinician in deciding the counselling, care and management of future pregnancies.